Analysis of factors of smart tourism development in Serbia - Savić, Jovana; Pavlović, Goran (Hotel and Tourism Management, 2018)
The rapid development of information technology has created numerous opportunities for the tourism sector. Smart tourism is one of the latest trends in tourism based on smart technologies. The aim of the research is to analyze the state of the key factors for the development of smart tourism in Serbia. Three factors were selected for the analysis: technology, human capital and innovation. The analysis relies on data on the state of these factors in the past five years from the reports on Serbia’s Competitiveness Index and comparing these data with data for countries in which smart city development initiatives have been launched. The conclusion drawn from the analysis is that Serbia has a good basis for the development of smart tourism from the point of view of technology and human capital, but that there is low innovative potential for it. Understanding these factors from the point of view of their past and current development, as well as level of development in relation to the countries in which smart cities exist, can help to determine to what extent and in which ways these factors can be improved in order to create the necessary conditions for development of smart tourism in Serbia.